Hubungan antara Dukungan Sosial dengan Kesejahteraan Psikologis pada Guru Honorer di Daerah Istimewa Yogyakarta - Zuhroh, Yumna Nafida; Winarsih, Tri (Universitas Muhammadiyah Metro, 2025)
Psychological well-being is very important to improve a person's optimal psychological functioning, good quality of life, and hope to live longer. Psychological well-being is influenced by many factors, one of which is social support because it functions as a mediator between stressors and individuals. Lack of social support for honorary teachers in the Special Region of Yogyakarta can make their psychological well-being level low. The purpose of this study was to determine the relationship between social support and psychological well-being in honorary teachers in the Special Region of Yogyakarta. The methodology used was a quantitative method with a correlational approach. A total of 100 honorary teachers in the Special Region of Yogyakarta became research subjects. The sampling technique in the study used accidental sampling. The data in the study were taken using a questionnaire and the data analysis used product-moment correlation analysis. The results of the correlation test between social support and psychological well-being showed r = 0.495 with a p-value = 0.000 (p < 0.005), which means that there is a significant relationship between social support and psychological well-being in honorary teachers in the Special Region of Yogyakarta.